Pelatihan Pembuatan Sabun dari Ecoenzym dan Limbah Minyak Goreng sebagai Rintisan Sociopreneur di Kalangan Ibu-Ibu Graha Aradea Rt. 04 Rw. 12 Desa Ciherang Bogor - Kusumayanti, Diah; Pambudi, Arde Lindung; Wibisono, Sandy (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Indonesia is a country that has abundant bio-elements. Indonesia also has a large population. This potential triggers an increase in the disposal of large amounts of waste and the absorption of large amounts of resource use in daily activities. Soap is a basic necessity that is used every day. The potential for managing waste from household activities to make soap is one solution to reduce waste disposal which can pollute the environment. Training on making soap from used cooking oil is one of the activities that can provide insight to the community regarding household waste management which can increase use value and added value. This training activity provides insight into making products that have selling value and insight into product marketing. This training activity also provides insight into how to make packaging, create attractive products and the sales potential for soap products from used cooking oil. Used cooking oil can also be used to make aromatherapy candles. This activity not only makes soap from used oil but also uses vegetable oil for bathing purposes using ecoenzymes. Ecoenzym is a product from the use of fermented fruit peel waste. Making soap from ecoenzymes can increase community empowerment regarding the added economic value of soap making. This activity is designed so that people can develop their own and their environment's potential to love the environment by managing waste well, thereby creating a clean and healthy environment and increasing family income. This activity can also support activities to form sociopreneurs in the Graha Aradea housing environment. Keywords: used cooking oil, soap, candles, sociopreneur